180-(6x+3+9x-3)=90

Simple and best practice solution for 180-(6x+3+9x-3)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 180-(6x+3+9x-3)=90 equation:



180-(6x+3+9x-3)=90
We move all terms to the left:
180-(6x+3+9x-3)-(90)=0
We add all the numbers together, and all the variables
-(+15x)+180-90=0
We add all the numbers together, and all the variables
-(+15x)+90=0
We get rid of parentheses
-15x+90=0
We move all terms containing x to the left, all other terms to the right
-15x=-90
x=-90/-15
x=+6

See similar equations:

| -28v=980 | | 6(5x+3)-6x=8x-(5+6) | | -133=3(4+6x) | | −(−b+5)+5b=−19−b | | 0.5(5-7x)=8=(4x+6) | | 8x=18.00/8 | | 6z+(10z-25)=18z+15-10z | | x=10/3x2+20x2 | | a−48=19 | | y=2y+50 | | 27n=351 | | B-2b=-5 | | 20−4h=–16−7h | | 6(5x+3)-6x=8x-3(3x+7) | | 2x+12=39-6 | | -60=70(x-0) | | 11/4=x/3 | | -5m-3m=-16 | | 11x^2=4+12x | | 35x+1.25=78.75 | | 6-(4*x+2)=12 | | 25=d/13 | | 80=100-x100 | | -5-3m=-16 | | x/15=18/2 | | x+2-5(x)=10 | | 8x-45=3x-5 | | -12.8=-2(p-6.3) | | P(a)=3/36 | | -3=5m-3-8m | | 11x^2=4+`12x | | 20-2(3x+10)=2x-3(3+x) |

Equations solver categories